Parâmetros bioquímicos sanguíneos, balanço de nitrogênio e metabolizabilidade da energia bruta em suínos alimentados com dietas contendo diferentes balanços eletrolíticos - Wochner, Mauricio Osvaldo; Pozza, Paulo Cesar; Nunes, Ricardo Vianna; dos Santos Pozza, Magali Soares; Lohman, Andre Cristiano; Bruno, Luis Daniel Giusti; Rodrigues, Mayara [UNESP]; Pasquetti, Tiago Junior (Universidade Estadual de Londrina (UEL), 2012)
The aim of this study was to evaluate different dietary electrolyte balance (DEB) on the blood biochemical parameters, nitrogen balances and crude metabolizable energy of swine in the initial phase. Sixteen barrows were used, averaging 27.95 kg of initial weight, allotted individually in metabolic cages in a randomized blocks design with four treatments (DEB of 160, 208, 257 and 305 mEq/kg) and 4 replicates. The blood biochemical parameters analyzed were chloride, potassium, sodium and urea in blood. Urine pH was also evaluated, and the parameters evaluated in nitrogen (N) balance were N intake, fecal N, N excreted in urine, absorbed N, N retention, retained N/absorbed N and total excretion of N. The gross energy digestibility and metabolizibility coefficients were determined, and the respectives values of digestible and metabolizable energy. The values of urinary pH increased (P < 0.01) linearly with increasing levels of DEB, ranging from 6.90 to 8.03. The results for chloride, potassium and nitrogen balances of variables and gross energy were similar (P > 0.05) between the evaluated DEB. A linear increase (P < 0.01) was also observed for sodium concentrations in blood serum due to the increase of DEB, with values of 2.91, 3.03, 3.27 and 3.18 g/l, respectively for the different treatments. Urea levels in blood serum increased linearly (P < 0.01), with values of 26.21, 28.64, 34.32 and 32.89 mg/dl. It was concluded that increasing the dietary electrolyte balance, from 160 to 305 mEq/kg resulted in higher concentrations of urea and sodium in blood serum, and higher pH values in the urine of swine in the initial phase.
Blood biochemical parameters, nitrogen balance and gross energy metabolizability in pigs fed with different dietary electrolyte balances
Keywords: Electrolytes; metabolizable energy; physiological parameters; sodium